Autistic nurses: do they exist? - Hedlund, Åsa (British Journal of Nursing, 2023)
Autism spectrum disorder is an increasing diagnosis on a global scale. Despite limitations related to the diagnosis, many people with autism are active in the workforce, often within the health care sector. It is reasonable to assume that some of those are nurses. There are very few examples of nurses with autism in the literature, mostly in non-scientific contexts, and that these mention both autism-related strengths and limitations at work. A conclusion is that research about nurses with autism is almost non-existent, and it is high time to conduct explorative research in this area. If employers are given the knowledge and the ability to support the needs of nurses with autism, it is likely to benefit the health of the individual nurse, the psychosocial working climate and patient safety.